Prospect of Poly(2-chloroaniline)-Nanocomposite-Silica as Anode in Li-Ion Coin Cell - Vani, G.; Jhancy Mary, S. (Asian Journal of Chemistry, 2021)
This work evaluates the application of interfacially polymerized poly(2-chloroaniline)-nanocomposite-silica (P2ClAni-SiO2), a composite material based on substituted conducting polymer, poly(2-chloroaniline) (P2ClAni) in which silica nanoparticles with varying weight percentages act as fillers. The nanocomposites were characterized by FTIR spectroscopy, XRD, TGA and DSC analysis. The electrochemical characterization of P2ClAni and P2ClAni-SiO2 (10 wt.%) were investigated by cyclic voltammetry, impedance spectroscopy and galvano-static cycling electrochemical measurements. The cyclic voltammogram studies showed broad redox peaks, which correspond to reversibility in transition of leucoemeraldine to emeraldine form of polyaniline. The charge transfer between electrolyte and electrode was represented in the form of Nyquist plot. The galvanostatic cycling test of P2ClAni and P2ClAni-SiO2 showed a discharge capacity of 44.3 mAh g-1 and 69 mAh g-1 for 5 cycles, respectively. P2ClAni-SiO2 composite shows good electrochemical properties and cycling stability compared to P2ClAni. The chlorosubstituted polyaniline with silica demonstrate to be an anode material in lithium ion batteries.